2001
DOI: 10.1112/s0025579300014339
|View full text |Cite
|
Sign up to set email alerts
|

Lattice points in lattice polytopes

Abstract: It is shown that, for any lattice polytope PaW 1 , the set int {P)nlZ d (provided that it is non-empty) contains a point whose coefficient of asymmetry with respect to P is at most Sd-(8/+1) 2 ' * . If, moreover, P is a simplex, then this bound can be improved to 8 ( 8 / + I ) 2 . As an application, new upper bounds on the volume of a lattice polytope are deduced, given its dimension and the number of sublattice points in its interior. §1. Introduction. A lattice polytope in W 1 is a convex polytope whose vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 8 publications
1
68
0
1
Order By: Relevance
“…Furthermore, int(Q) ∩ Λ = ∅ since P is properly contained in Q and P is maximal Λ-free. 2d+1 (see [Pik01]). …”
Section: Relint(p ) ∩ λ Consists Of Precisely One Pointmentioning
confidence: 99%
“…Furthermore, int(Q) ∩ Λ = ∅ since P is properly contained in Q and P is maximal Λ-free. 2d+1 (see [Pik01]). …”
Section: Relint(p ) ∩ λ Consists Of Precisely One Pointmentioning
confidence: 99%
“…If P is canonical, Pikhurko [46] gives an upper bound on the sum of the weights h  2 3n 2 15 (n 1)2 n+1 . In dimensions two and three this is far from sharp (the maximum values are 1 + 2 + 3 = 6 and 5 + 6 + 22 + 33 = 66, respectively).…”
Section: Fano Simplicesmentioning
confidence: 99%
“…Convex and discrete geometry: Given a d-dimensional lattice polytope P with only one lattice point in its interior, Hensley [13] showed that the volume and the number of lattice points of P is bounded above by a function depending only on d. In [21] and [25] asymptotically better upper bounds were obtained. However, in lower dimensions they are presumably still very far from being sharp, cf.…”
Section: Introductionmentioning
confidence: 99%
“…This bound vastly improves on general upper bounds on the volume of lattice simplices containing only one lattice point in the interior, as given in [21] or [25].…”
mentioning
confidence: 99%